2008
DOI: 10.1016/j.pediatrneurol.2007.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Autoregulation After Pediatric Traumatic Brain Injury

Abstract: Traumatic brain injury is a global health concern and is the leading cause of traumatic morbidity and mortality in children. Despite a lower overall mortality than in adult traumatic brain injury, the cost to society from the sequelae of pediatric traumatic brain injury is very high. Predictors of poor outcome after traumatic brain injury include altered systemic and cerebral physiology, including altered cerebral hemodynamics. Cerebral autoregulation is often impaired following traumatic brain injury and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 116 publications
1
72
0
11
Order By: Relevance
“…Reduced CBF is consistent with published data of alterations in CBF following TBI in both humans and animal models. 96,97 This reduced flow is also supported by data provided by the third instrumentation setup (Sec. 3.3).…”
Section: Discussionsupporting
confidence: 53%
“…Reduced CBF is consistent with published data of alterations in CBF following TBI in both humans and animal models. 96,97 This reduced flow is also supported by data provided by the third instrumentation setup (Sec. 3.3).…”
Section: Discussionsupporting
confidence: 53%
“…14 Paralleling the structural changes are changes in cerebral glucose metabolism and cerebral blood flow. 25 Although post-concussed adolescent athletes often display no gross neural pathologies and have no immediate threat to their life, profound biochemical changes induced by injury in immature, highly-sensitive structures (e.g., the prefrontal cortex, hippocampus, hypothalamus) during this critical developmental stage can increase risk for several neuropsychiatric conditions, with farreaching acute and chronic systemic effects. Brain injury, of any severity, in the developing brain is complicated by ongoing cerebral maturation.…”
Section: Casazza K Et Al: Nutrition In Sports-related Concussionmentioning
confidence: 99%
“…Cerebral vasodilation, as well as the increase in cerebral blood volume for which it is responsible (the final common pathway for ICP plateau waves whatever the underlying pathology), is in craniosynostosis a primary rather than a secondary phenomenon due to the rise in PaCO 2 (hypercapnia) related to the airway obstruction that occurs particularly during REM, or active, sleep. 26 The extreme sensitivity of the cerebral arterioles to such alterations in PaCO 2 ("cerebral blood flow increases linearly by 2%-4% per mm Hg PaCO 2 within the range of 25-75 mm Hg, making PaCO 2 the most potent physiologic cerebral vasodilator" 77 ) is a further indication of a functioning autoregulatory system.…”
Section: Autoregulationmentioning
confidence: 99%
“…According to one study, "data from healthy anesthetized children suggest that CO 2 vasoreactivity is higher in children than in adults." 77 In a study that used TCD ultrasonography during low-dose sevoflurane anesthesia to investigate cerebral autoregulation in 52 children ages 6 months-14 years and compared it to that in 12 adults, Vavilala et al 80 found "no age-related differences in autoregulatory capacity [and] no differences in autoregulatory capacity between children and adults." In a complementary study 79 (this time in 53 children ages 6 months-14 years) of the lower limits of autoregulation as well as autoregulatory reserve, the authors concluded that "increasing age appears to confer some margin of safety against cerebral hypoperfusion," but they attributed this to "physiologically normal age-related increases in MAP [mean arterial pressure]" rather than any age-related variability in autoregulatory abilities.…”
Section: Age-related Susceptibility Of the Brainmentioning
confidence: 99%